PEMBANGUNAN APLIKASI SELEKSI PESERTA DIDIK BARU SMK2 SURAKARTA DENGAN METODE AGILE EXTREME PROGRAMMING - Arief Nur Huda; Faisal Najib; Hidayat Abdul Rouf; Rini Anggrainingsih; Viki Dwi Kusnandar (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2017)
This paper reports development an admission new students application for support selection process in SMKN 2 Surakarta.Software development model for this application used Waterfall method through stages of analysis, design, implementation and testing phases.Testing on correctness factor showed that this application qualifies user requirement specification of SMK N 2 Surakarta. Testing on reliability factor performed using Apache JMeter software and obtained the result that as many as 20 users did not experience a failure accessing applications simultaneously, whereas the "input weights" and the "calculation" pages could only be accessed by single user. Testing on efficiency factor performed using GTMetrix website, obtained grade A in PageSpeed Score and grade A in YSlow test. Based on the testing result, this application can be used to help in the selection of the new students at SMK N 2 Surakarta.